Remedial exercise training program (aerobic and brisk walk training) for type II diabetes (T2DM) - Vinu W; Vinod Kuamr (Universidad de Murcia, 2024)
Diabetes type 2 Mellitus (T2DM) is a severe world crisis. The Indian population, mostly above forty years' age group they sick with Diabetes. Most doctors prescribe walking as an endurance activity to improve diabetic patients. Therefore, the aim of this study was to investigate the effect of aerobic exercise, including spot jogging, stepping, jumping exercises and simple dance movements, together with brisk walking on the improvement of type II diabetes. Ten subjects with type II diabetes mellitus (T2DM) were selected as participants for this study. Totally 12 weeks of training was executed for this diabetes group, the training intensity was followed beginning with two minutes of continuous exercises with one-minute rest interval, and it has been progressively increased. The timing and intensity continue to forty minutes with five minutes' rest intervals to reach to find the improvement in Type II diabetes. Statistical Package for Social Sciences version 21.0 was used to analyze the data. Aerobic exercises and brisk walking significantly reduced the body weight, blood sugar level and showed significant changes in the systolic and diastolic blood pressure of type II diabetes.